Gene action and heterosis studies for yield and its components in upland rice - Kumar, Abhishek; Pandey, Deo Prakash (Journal of Cereal Research, 2024)
The present study was conducted to work out gene action and heterosis studies using Line × Tester mating design in rice using 10 lines suitable for rainfed upland conditions of H.P. and 3 testers in Kharif 2021 and 2022 (for crossing and evaluation, respectively). The per cent narrow sense heritability was low (<50%) for all the traits and among them the highest h2ns was shown by spikelet fertility (10.09) followed by grain Breadth (10.06) and spikelet per panicle (9.79). This also indicates the preponderance of non- additive genetic variance in the inheritance of these traits.The cross combinations that showed significantly high heterosis over the standard check for grain yield per plant were HPR 2559 x HPR 2795 (91.62%), HPR 2559 x HPR 1156 (72.81%), HPR 2645 x HPR 2656 (65.65%), and HPR 2830 x HPR 1156 (58.82%).